Utilization of tanniniferous feeds. 3 Effect of ferrous sulphate treatment of babul pods (Acacia nilotica) on nutrient utilization and tannin degradatiion - BARMAN, K; RAI, S N (The Indian Journal of Animal Sciences, 2011)
Ferrous sulphate (FeS04) was used at 0, 0.5, 1.0, 1.5, 2.0,2.5 and 3.0% levels at 30 and 40% moisture level for 1, 3 and 5 days reaction period to inactivate the tannin of babul pods. Treatment was ineffective in increasing the in vitro nutrient digestibility. However, in vitro DM, OM and gas production were improved at 30% moisture level for 3 days reaction period. Reaction period can be reduced to 1 day by increasing the moisture level from 30 to 40% with a similar effect. It is inferred that ferrous sulphate is ineffective fro inactivation of babul pods tannins.Â